2007
DOI: 10.1002/gps.1852
|View full text |Cite
|
Sign up to set email alerts
|

The effects of antidepressant medication adherence as well as psychosocial and clinical factors on depression outcome among older adults

Abstract: Interventions should be directed toward improving antidepressant adherence and modifiable psychosocial variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 47 publications
2
37
1
1
Order By: Relevance
“…A growing body of literature has also shown that these psychosocial factors influence depressive symptoms even in the context of pharmacotherapy (e.g., Bosworth et al, 2008; Pedrelli et al, 2008). Additionally, some earlier studies suggested that ethnicity might play a role in treatment outcomes of those undergoing pharmacotherapy for depression (e.g., Wagner et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of literature has also shown that these psychosocial factors influence depressive symptoms even in the context of pharmacotherapy (e.g., Bosworth et al, 2008; Pedrelli et al, 2008). Additionally, some earlier studies suggested that ethnicity might play a role in treatment outcomes of those undergoing pharmacotherapy for depression (e.g., Wagner et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to various life stressors and chronic interpersonal stress has been consistently linked to the onset and course of major depression (Hammen, 2003; Kendler et al, 1999; Kendler et al, 2004; Kendler et al, 1997; see Kessler, 1997 for a review). However, the evidence linking stress to antidepressant response has been mixed, with some studies suggesting that there is no relationship between stress and depression in the context of antidepressant treatment (Bosworth et al, 2008), some showing that stress is associated with worse treatment outcomes (Mazure et al, 2000; Pedrelli et al, 2008; Tomaszewska et al, 1996), and others suggesting that interpersonal stress is associated, counter-intuitively, with better treatment outcomes (Sherbourne et al, 2004; Vallejo et al, 1991). …”
Section: Introductionmentioning
confidence: 99%
“…Older adults usually present with mental health issues in primary care settings, where medications are much more readily available than psychotherapy and where quality of care is usually lower compared to specialty mental health settings (Wang et al 2005). Older adults do not adhere to psychotropic medication regimens (Bosworth et al 2008), and most prefer psychotherapy (Gum et al 2006). Meta-analyses have demonstrated that psychotherapy is effective (Pinquart et al 2006), and that older adults benefit from psychotherapy just as well as younger adults (Cuijpers et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Within two years 60% of community-dwelling older adults with MDD became depressed again unless they were maintained on antidepressant medication [13]. Poor adherence to taking medications may account for a substantial proportion of treatment failures [14, 15]. Patients' compliance and continuous treatment are important.…”
Section: Introductionmentioning
confidence: 99%